PARENTING ISLAMI BERBASIS PENGAJIAN DALAM MEMBENTUK PEMAHAMAN ORANG TUA TENTANG STIMULASI PERKEMBANGAN ANAK USIA DINI - Karyamah, Imas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This qualitative descriptive study examines how an Islamic parenting program embedded in a recitation forum (pengajian) shapes parents’ understanding of early childhood developmental stimulation at RA Al Hidayah Bandung. Data from in-depth interviews with six informants, observation, and documentation were coded and triangulated. The program runs routinely and is integrated with the school, with its strength in the consistent integration of Qur’anic and hadith values and parents’ trust in the da’iyah. Parents’ understanding is strong but uneven—robust in the religious-moral, language, and social-emotional aspects, yet weak in the cognitive, physical-motor, and artistic domains. Understanding is shaped through lecturing, dialogue, and exemplary conduct, extending into observable changes in parenting practice. The program is an effective community non-formal education channel, though its governance and curriculum remain at an early stage of institutionalization. Keywords: early childhood stimulation, Islamic parenting, non-formal education, parental understanding, recitation forum